2015
DOI: 10.14260/jemds/2015/2566
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Role of Per-Operative Peritoneal Lavage With Super Oxidized Solution in Perforation Peritonitis

Abstract: BACKGROUNDThe fundamental in treatment of perforation peritonitis include resuscitation, treatment of septicemia, control of contaminating source and peritoneal toilet. Numerous studies have shown the role of different solutions such as normal saline, antibiotics and betadine as peritoneal lavage in reducing morbidity and mortality of perforation peritonitis. The objective of this study was to present our finding on the role of per-operative peritoneal lavage with super-oxidized solution in cases of perforatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, peritoneal lavage with super-oxidized solution has shown decreased surgical site infection and mortality incidence in emergency laparotomies 8 . However, one study showed that there was no clinical outcome difference between using super-oxidized solution or normal saline alone as a peritoneal lavage fluid 11 .…”
Section: Indications For Different Agents In Peritoneal Lavagementioning
confidence: 99%
“…Moreover, peritoneal lavage with super-oxidized solution has shown decreased surgical site infection and mortality incidence in emergency laparotomies 8 . However, one study showed that there was no clinical outcome difference between using super-oxidized solution or normal saline alone as a peritoneal lavage fluid 11 .…”
Section: Indications For Different Agents In Peritoneal Lavagementioning
confidence: 99%